QUANTIFICATION OF TOTAL FLAVONOID CONTENT IN FRACTIONATED YOUNG LEAF EXTRACTS OF RED SHOOT LEAVES (Syzygium myrtifolium) USING UV-VIS SPECTROPHOTOMETRY - Vilya, Syafriana; Rika, Amelia; Nissa, Maftucha; Munawarohthus, Sholikha; Windri, Handayani; Yasman, Yasman (Pharmacoscript, 2025)
Syzygium myrtifolium (red shoot leaves) is widely known for its rich phytochemical profile, particularly flavonoids, which exhibit various pharmacological properties. This study aimed to determine the total flavonoid content in the crude extract, n-hexane fraction, ethyl acetate fraction, and water fraction of red shoot leaves (Syzygium myrtifolium) using a colorimetric method with quercetin as a standard. The results revealed that the ethyl acetate fraction had the highest flavonoid content (65.781 ± 6.365 mgQE/g), followed by the crude extract (26.093 ± 0.961 mgQE/g), n-hexane fraction (18.293 ± 2.925 mgQE/g), and water fraction (12.583 ± 0.824 mgQE/g). The study also found that the solvent polarity significantly influenced the flavonoid extraction efficiency, with ethyl acetate, a moderately polar solvent, being most effective for isolating flavonoid aglycones. The n-hexane fraction contained polymethyl flavonoids, which are more soluble in nonpolar solvents, while flavonoid glycosides were more soluble in polar solvents like water and alcohol mixtures. Furthermore, the research highlights the importance of extraction methods, as the total flavonoid content in mature red shoot leaves was found to be higher than in younger leaves, likely due to increased secondary metabolite production in mature tissues. This study emphasizes the role of solvent polarity in flavonoid extraction and provides insights into the phytochemical composition of S. myrtifolium leaves for potential applications in natural product research.